Генерацiя звуку обмеженою областю збуреної течiї в нескiнченнiй прямiй жорсткостiннiй трубi кругового поперечного перерiзу. Спрощена форма розв’язку - Борисюк, А.О. (Видавничий дім "Академперіодика" НАН України, 2007)
Another form of a solution to the problem of sound generation by a limited region of the disturbed flow in an infinite straight rigid-walled pipe of a circular cross-section is presented. This form is more simplified compared to that obtained earlier and is more acceptable for making the corresponding calculations.